The Dermatology Provider's Role in the Antibiotic Resistance Crisis: An Update on Alternative Treatments for Acne Vulgaris. Issue 2 (March 2021) - Dadrass, Farinoosh; Lake, Eden
Abstract : ABSTRACT: Dermatology healthcare providers commonly treat acne vulgaris with oral and topical antibiotics. In the face of the current antibiotic resistance crisis, alternative therapies should be considered prior to the use of antibiotics and antibiotics should be used sparingly. Alternative therapies include retinoid therapies, retinoid combination therapies, hormonal therapies, and light-based therapies, as well as various combinations of these therapies. Patients would benefit from the initial exclusion of an underlying endocrine pathology prior to initiating vitamin A-derived therapies, light-based therapies, or more subtle hormonal therapies.